RHIZOME YIELD OF TEMULAWAK (Curcuma xanthorrhiza Roxb.) AT N, P, K VARIOUS LEVEL AND N, K COMBINATION - Nihayati, Ellis; Wardiyati, Tatik; Sumarno, Sumarno; Retnowati, Rurini (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
The role of N, P and K on temulawak have not been clear enough to explain the need in temulawak rhizome in order to get high yield. The experiment was conducted in a screen house in Malang East Java with an altitude of 500 m asl. from Desember 2010 - August 2011. There were 4 experiments in series, consisting of N, P, K various level and N,K alone and combination on the growth and quantity of rhizome arranged in randomized block design comprising 7 levels of fertilizer per plant with 3 replications. The treatments of urea (N), SP36 (P) consisted of 0, 1,25, 2,5, 3,75, 5, 6,25 and 7.5 g. The KCl (K) comprised 0, 1,5, 3, 4,5, 6, 7,5 and 9 g. The N, K alone and combination treatments consisted of (No fertilizer, N, K, NK g /plant). The results of this research were N, P, K optimum dose of each N 6.25 g N / plant P2O5/tan P 6.25 g, K 7.5 g K2O / plant increased temulawak rhizome dry weight. Combination 4.5 g N + 2.8 g K / plant could increase temulawak rhizome dry weight by 33% compared to the addition of N and 220% when compared to the addition of a single K harvesting age 6 months. Keyword : Curcuma xanthorriza, rhizome, N, P, K.